Exploring the ferromagnetic behaviour of a repulsive fermi gas through spin dynamics - Valtolina, Giacomo; Amico, Andrea; Enss, Tilman (Nature physics, 2017)
Can short-range repulsion alone bring a system into the ferromagnetic phase? The question is explored by investigating the spin dynamics in a resonantly interacting ultracold Fermi gas, and a Stoner-like ferromagnetic instability is observed.